Women and War: Women's Rights in Post-Civil War Society. Issue 2 (2nd July 2020) - Gurses, Mehmet; Arias, Aimee; Morton, Jeffrey
ABSTRACT: To what extent do women's rights change in a post-civil war society, and what explains these changes? To address these questions, a number of studies emphasise the disruptions to daily home, work, and community environments brought about by the dynamics of conflict. While war is disruptive and has the potential to generate new opportunities for women, we argue that conflict alone fails to explain variations in women's rights. Using a cross-sectional dataset, we examine the insurgent group's political ideology as a central explanatory factor for changes in women's rights in the aftermath of civil war. Results from a series of regression analyses show that while wartime dynamics help improve women's political rights, this is not necessarily the case when it comes to women's economic and social rights. These results demonstrate the need to account for the insurgent group's political ideology in examining the change to women's rights in the context of armed conflict.